1988
DOI: 10.1017/s0003356100003317
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hormone and metabolite concentrations in different breeds of beef steer on two systems of production

Abstract: Request Permissions : Click here Downloaded from http://journals.cambridge.org/ASC, IP address: 128.218.248.200 on 12 Apr 2015Anim. Prod. 1988. 47: 231-244 (>()(>3-3561/88/7()7l()231$()2-0() ABSTRACTThe experiments were conducted to investigate the effect of sire breed and production system on serum GH, insulin, prolactin, glucose and blood urea nitrogen concentrations in growing beef cattle. A total of 187 steers, representing a wide range of maturity types, was reared to slaughter on either the 16-month o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
2
4
1
Order By: Relevance
“…The lower urea concentration of the dairy strains compared to the beef breeds during the first winter and at slaughter is in agreement with the findings of Clinquart et al (1995) who compared purebred Belgian Blue and Holstein bulls. The higher urea concentrations of AA compared to BB during the second winter and at slaughter are consistent with the findings of Beeby et al (1988) who observed higher urea concentrations in early than in late maturing steers. These authors attributed this finding to the early maturing steers requiring less of their protein intake for muscle growth with the excess being deaminated.…”
Section: Blood Metabolite Concentrationssupporting
confidence: 90%
See 1 more Smart Citation
“…The lower urea concentration of the dairy strains compared to the beef breeds during the first winter and at slaughter is in agreement with the findings of Clinquart et al (1995) who compared purebred Belgian Blue and Holstein bulls. The higher urea concentrations of AA compared to BB during the second winter and at slaughter are consistent with the findings of Beeby et al (1988) who observed higher urea concentrations in early than in late maturing steers. These authors attributed this finding to the early maturing steers requiring less of their protein intake for muscle growth with the excess being deaminated.…”
Section: Blood Metabolite Concentrationssupporting
confidence: 90%
“…As there were generally only small differences between the genetic merit groups in DMI (Campion et al, 2009) significant effects on blood metabolite concentrations were not expected, as energy status rather than genotype of the animal, is the main determinant of blood metabolite concentration (Beeby et al, 1988;Spicer et al, 1990). This is supported by the significant effect of first winter feeding level on blood metabolite concentrations.…”
Section: Blood Metabolite Concentrationsmentioning
confidence: 94%
“…To evaluate the effect of age uninfluenced by stress sequential samples were taken by means of catheter. On a low plane of nutrition GH concentrations were increased in steers (Beeby, Haresign and Swan, 1988) whereas in the present trial, no consistently enhanced effect on GH levels was visible on a low plane of nutrition. However, the magnitudes were lower in the current samples obtained by catheter, which would suggest that stress enhanced GH concentrations when samples were taken by needle puncture, involving the handling of the animal, particularly in bulls.…”
Section: Discussioncontrasting
confidence: 78%
“…This breed difference in plasma insulin is similar to the result reported by Grigsby and Trenkle (1986), who observed higher plasma insulin concentrations in small-framed Angus steers than in larger Limousin or Simmentals. Other workers (Roy et al, 1983;Beeby et al, 1988) have also reported higher levels of insulin in Aberdeen Angus-cross animals than in other latematuring steers. Conversely, Verde and Trenkle (1987) reported that large steers had higher insulin concentrations than small steers, which was related to the greater feed intake of the large animals.…”
Section: Discussionmentioning
confidence: 83%
“…Blood insulin concentration increases with age and BW in cattle (Trenkle, 1970;Martin et al, 1979). Several workers (Roy et al, 1983;Grigsby and Trenkle, 1986;Beeby et al, 1988) have reported greater insulin concentrations in smaller, early-maturing breeds of cattle than in larger, late-maturing breeds, although the converse has also been noted (Verde and Trenkle, 1987). Trenkle and Topel (1978) reported that plasma insulin concentration was positively correlated with carcass fat and negatively correlated with carcass muscle.…”
Section: Introductionmentioning
confidence: 98%